Mechanisms of hypersensitivity reactions induced by drugs - Franceschini, Fabrizio; Bottau, Paolo; Caimmi, Silvia; Cardinale, Fabio; Crisafulli, Giuseppe; Liotti, Lucia; Saretta, Francesca; Bernardini, Roberto; Mori, Francesca; Caffarelli, Carlo (Acta Biomedica Atenei Parmensis, 2019)
Adverse drug reactions include drug hypersensitivity reactions (DHRs), which can be immunologically mediated or non-immunologically mediated. The high number of DHRs unconfirmed and/or self-reported is a frequent problem in daily clinical practice, with considerable impact on future prescription choices and patient health. It is important to distinguish between hypersensitivity and non-hypersensitivity reactions by adopting a structured diagnostic approach to confirm or discard the suspected drug, not only to avoid life-threatening reactions, but also to reduce the frequent over-diagnosis of DHRs.